The Current State of Bashkir Song Folklore: A Case Study of 21st-Century Expeditional Materials - Aigul M. Khakimyanova (Oriental Studies, 2021)
Introduction. At present, people’s interest in the historical and ethnocultural heritage has increased, and the desire to preserve traditional values for future generations has grown stronger. Song recordings made in the 19th – 20th centuries are evidence of the developed musical and song tradition of the Bashkir people. Due to the collecting efforts of M. A. Burangulov, A. N. Kireev, S. A. Galin, N. D. Shunkarov and others, a whole layer of folk songs has been preserved. During expeditions that have been intensified since the beginning of the 21st century by the Institute of History, Language and Literature of the Ufa Scientific Center of the Russian Academy of Sciences, folklorists are working hard to multifacetedly cataloguize folk knowledge, on the basis of which one can judge the state of traditional modern folklore of the Bashkirs. In our understanding, ‘modern folklore’ is folklore that has existed since the middle of the 20th century to the present, regardless of the environment of existence. Goals. This work aims to consider the genres of traditional musical folklore of the Bashkirs that have survived today, to give a brief description of them, and also to analyze them from the viewpoint of assessing the modern spiritual state of the ethnos. Unlike other genres, musical genres are well preserved in the memory of the population. It is the song and takmaks that are the main genres of modern Bashkir oral and poetic creativity, which makes it possible to reveal the dynamics of the development of folklore. Materials and Methods. The research is based on the author’s expedition materials collected in the 21st century in different regions of the Republic of Bashkortostan and beyond, where the Bashkirs live compactly. They retain collective axiological attitudes and serve as a way of expressing shared emotions. These genres have a high level of demand among the population and therefore quantitatively prevail in expedition records. Folk songs are kept in the memory of people — bearers of folk musical culture, and are not recorded by them in writing. The transmission of musical and folklore works occurs orally. This means that any folk song is perceived and absorbed by each new generation by ear directly at the moment of sounding. Occasionally, songs can be recorded along with their stories and legends. The availability of songwriting histories is a characteristic feature of Bashkir folk songs. Many songs lose their names over time, but they do not completely disappear from the memory of the people, as evidenced by the comments of informants characterizing these works in expressions, such as ‘my mother’s song’, ‘this song was performed by my father’, etc. This phenomenon reflects the strong cultural connection between generations, when performers with special trepidation cherish the memory of their relatives and can reproduce the tune once performed by their father or mother. Along with drawling songs, short four-line songs without a title, drinking songs and takmaks are also common. Takmaks, in turn, are distributed not only orally but also in writing. Modern takmaks are distinguished by great mobility and efficiency, they instantly respond to urgent problems. In the light of recent events, takmaks have appeared on the topic of a pandemic, self-isolation, and online training. Results. A review of folklore materials collected in recent decades shows that the musical genres of Bashkir folklore continue to exist, which means that it is necessary to study not only the current state of the Bashkir song heritage but also its evolution. The folk song, folk singing traditions must be passed on to the younger generation, and only then the folk culture will develop and be preserved for future generations